Utilización de lectinas h y a1 en la tipificación sanguínea directa del sistema abo como control de calidad de los resultados de grupos sanguíneos obtenidos en usuarios atendidos en el laboratorio clínico del hospital civil de alausí durante el periodo junio – agosto del 2010 - Orozco, Lorena (2010)
The present investigative work was spoken fundamentally of the "Lectinas use H and A1 in the direct sanguine typifications of the system ABO like control of quality of the results of sanguine groups obtained in users assisted in the Clinical Laboratory of the Civil Hospital of Alausí during the period June - I Wither of the 2010" since he/she has vital importance in the field of the Inmunohaematology and Medicine Transfusional as well as to the students of different specialties of the health, it stops this way to avoid reactions transfusionales in patients that needed it.